2019
DOI: 10.3389/fnagi.2019.00126
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Capacity as a Predictor of Cognitive Training Efficacy in the Elderly Population

Abstract: Aging is associated with a decline in a wide range of cognitive functions and working memory (WM) deterioration is considered a main factor contributing to this. Therefore, any attempt to counteract WM decline seems to have a potential benefit for older adults. However, determination of whether such methods like WM trainings are effective is a subject of a serious debate in the literature. Despite a substantial number of training studies and several meta-analyses, there is no agreement on the matter of their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 102 publications
(119 reference statements)
2
57
0
4
Order By: Relevance
“…We found evidence that WMT, irrespective of baseline or adaptive protocol, improved the score of the dual n-back task played by the participants at the post-training in comparison with the pre-training session, in agreement with past studies using fewer sessions of WMT [39]. Our training protocol lasted 20 days, a duration comparable with other studies reported in the literature using Dual n-Back Task [64]. In addition to increase in dual n-back scores in controls, we observed that WMT improved performance in the WAIS-IV Digit Span in agreement with previous studies [39,65,66].…”
Section: Discussionsupporting
confidence: 89%
“…We found evidence that WMT, irrespective of baseline or adaptive protocol, improved the score of the dual n-back task played by the participants at the post-training in comparison with the pre-training session, in agreement with past studies using fewer sessions of WMT [39]. Our training protocol lasted 20 days, a duration comparable with other studies reported in the literature using Dual n-Back Task [64]. In addition to increase in dual n-back scores in controls, we observed that WMT improved performance in the WAIS-IV Digit Span in agreement with previous studies [39,65,66].…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, in elderly adults, we observed a completely different structure of the sensor-level functional connectivity, i.e., a stronger coupling between the frontal, central-parietal, and bilateral temporal EEG sensors with the most influential node located in the central EEG row (Cz sensor). As the working memory decline with age is well-documented [ 61 63 ], we conclude that memory representation of motor actions is less accessible in elderly adults. Based on our findings and the existing literature, we suggest that higher coupling within the sensorimotor area during a pre-movement phase in the elderly group indicates the prevalence of sensorimotor integration mechanisms relative to the resource-demanding Bland’s Type 1 motor-related theta activation [ 25 ].…”
Section: Discussionmentioning
confidence: 56%
“…Previous training studies with OAs yielding data that speak to these two accounts have revealed mixed results, either supporting the compensation account (López-Higes et al, 2018;Roheger, Meyer, Kessler, & Kalbe, 2019;Witlock, McLaughlin, & Allaire, 2012;Zinke et al, 2014), the magnification account (Matysiak, Kroemeke, & Brzezicka, 2019), or both (depending on the type of transfer task: Borella et al, 2017). A recent study by Fu, Maes, Kessels, and Daselaar (2017) provided support for the magnification account.…”
Section: Introductionmentioning
confidence: 97%